Field based model for pedestrian dynamics. (1st March 2018) - Yu, Bin; Zhang, Michael; Wang, Zhongren
Abstract: A pedestrian's physical movement is simulated as a response to the pedestrian subjective evaluation of the objective environment. The objective environment is modeled by presumed fields statically or dynamically superposed. Regulation functions, which consider not only force caused by presumed fields but also local crowd densities around pedestrians, are introduced for consideration of pedestrians' intelligence. Numerical experiments indicate that the model can be calibrated to reproduce a fundamental diagram that matches an empirical one proposed by Weidmann. Such experiments prove the model to be a useful tool for study of pedestrian dynamics.